Faktor Mempengaruhi Perilaku Antisosial Siswa: Tinjauan Literatur dan Intervensi Konseling - Mutia Najwa Khairunnisa; Oktavia Utami Ramadhani; Okti Pravitasari; Annisa Nasywa Kalyca; Rizki Novirson; Resti Okta Sari (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2026)
Antisocial behavior is a psychosocial phenomenon that has a significant impact on individual development and the educational climate in schools. This behavior is characterized by violations of social norms, aggressiveness, low empathy, and withdrawal from the social environment. This article aims to comprehensively examine the causes, manifestations, and counseling intervention strategies in dealing with antisocial behavior in students. The method used is a literature review by examining 15 scientific articles that meet the research relevance criteria. The results show that antisocial behavior is influenced by internal factors such as depression, low moral identity, and moral disengagement, as well as external factors such as parenting patterns, peer interactions, and social media use. Effective intervention strategies include group counseling services, religious approaches, collaboration between schools and families, and character education reinforcement. These findings emphasize the importance of guidance and counseling in the early detection, prevention, and comprehensive management of antisocial behavior in educational settings.